Characteristics of Successful Alternative School Programs... - Michels, Bob (Horyzonty Wychowania, 2017)
This article looks at some of the successful components andcharacteristics of Best Practices in the United States and analyzeswhy some programs work and why others do not. It alsodiscusses non-conventional and antisocial youth who are in ourschools as well as strategies to assist in resolving and changingtheir behaviors.Looking at predisposing factors leading to delinquency, antisocialbehavior and criminal factors are also reviewed as well as characteristicsof a successful teacher in an alternative school setting.